Antecedents of export performance: the case of the Turkish textile and apparel industry - Parlakgül, Murat. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
Ever-changing global conditions directly affect the firms and their international involvement. Therefore, the firms should chose a position and use their resources so that they can maintain their competitive advantages and keep away from the risks of the new situation. This study employs the Resource Based View (RBV) of the firm in order to identify several human capital, physical capital and organizational capital resources with positive export performance implications. The effect of factors internal to the firms and are uncontrollable in the short run are analyzed. The proposed export performance model is tested using nonparametric statistical techniques on a sample of 58 Turkish exporters all from textile and apparel industry. The impact of eight characteristics categorized under two groups as managerial characteristics (manager’s education, manager’s international experience) and firm characteristics and competencies (firm size, firm’s age, Eximbank supports, business group affiliation, R&D expenditure and innovativeness) on export performance is analyzed. Four of these characteristics - manager’s education, manager’s international experience, Eximbank supports and R&D expenditure - are found to be positively and significantly related to the export performance while other four variables - firm size, firm’s age, business group affiliation and innovativeness- had insignificant relationships. This study is the first industry specific study which takes into account the lagged effect of R&D expenditure on export performance in Turkish context.
Keywords: Export marketing -- Turkey.; Textile industry -- Turkey.